Frog music [compact disc, unabridged] : a novel - Donoghue, Emma, 1969- (Hachette Audio, 2014)
San Francisco, 1876, is having a heatwave to break all records and there is an outbreak of smallpox as well. Jenny is shot dead in a railway station, but her friend Blanche survives. Blanche vows to do everything she can to find Jenny's killer. As she searches, she finds out that Jenny had a secret life: that she was a notorious law-breaker and charmer, a free-love bohemian who mixed in with a dangerous crowd. As Blanche pieces the story together, Jenny's murderer may be coming after her next.